2018
DOI: 10.3136/fstr.24.159
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Suitability of Boiled Pasta with Tomato Sauce for Eating

Abstract: Pasta samples boiled for different times and mixed with tomato sauce were physically and chemically evaluated to determine the factors affecting the suitability of boiled pasta with tomato sauce for eating. Physical properties of the pasta boiled for the shortest time changed greatly when sauce was added. The texture of the pasta boiled for the longest time was soft, because the core lacked a non-gelatinized region. In a force-strain curve, the change in the force after the breaking point of the pasta boiled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…Mie lidi disajikan dengan ditambah saus morenggo yang dibuat berdasarkan penelitian sebelumnya (Komariah, 2011) guna meningkatkan daya tarik dan gizi (Nakanishi et al, 2018). Modifikasi dilakukan dengan menambahkan garam untuk menetralisir bau apek (Shere et al, 2018).…”
Section: Uji Organoleptik Mie Lidiunclassified
“…Mie lidi disajikan dengan ditambah saus morenggo yang dibuat berdasarkan penelitian sebelumnya (Komariah, 2011) guna meningkatkan daya tarik dan gizi (Nakanishi et al, 2018). Modifikasi dilakukan dengan menambahkan garam untuk menetralisir bau apek (Shere et al, 2018).…”
Section: Uji Organoleptik Mie Lidiunclassified
“…Mankind is utilising plant extracts and oils for thousands of years for many purposes including food preservation and therapeutics (Hammer, Carson & Riley, 1999). Plant-based foods are prone to deteriorate at some rate after harvesting due to physical interventions, and chemical and microbial reactions (Nakanishi, Irie & Murata, 2018;Thielmann, Kohnen & Hauser, 2017) types of methods such as freezing, smoking, heating, sun drying, irradiation and chemical treatments are in place alone or in combination for preservation of foods. A global estimate for food loss has revealed that 10% of cereal and 40% of vegetables and fruits, including 75% of peas and beans are lost during storage every year.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of sugar cane concentration on foam-mat drying kinetics and physicochemical properties of dried-tomato pasta sauce INTRODUCTION Pasta, including spaghetti, is generally served with tomato sauce (Nakanishi et al, 2018). Pasta sauce is sugar-rich food formulated using tomato paste and sugar.…”
mentioning
confidence: 99%